St. Vincent and the Grenadines : 2003 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for St. Vincent and the Grenadines. (IMF Staff Country Reports; Country Report ;, 2005)
St. Vincent and the Grenadines's 2003 Article IV Consultation reports that it had moderate levels of public sector debt and debt service during the 1990s. To reduce growth volatility, since the mid-1990s, the government has attempted to implement an economic diversification program supported by major public investments. The cornerstone of the economic diversification program has been structural reforms in the agricultural sector, aimed not only at promoting nonbanana crops, but also at increasing the productivity of the banana sector.